Uniformização de jurisprudência e vinculação - Donelian, Archavir Mário (2020)
The purpose of this dissertation is to analyze the binding effects of the guidelines resulting from the forms of standardization of the case law in the Code of Civil Procedure, Law No. 13,105, of March 16, 2015. Laws no. 11.417, of December 19, 2006, 9.868, of November 10, 1999, and 9.882, of December 3, 1999, due to existing references to institutes regulated by them in the Code of Civil Procedure, were also analyzed. The assumptions adopted were that there is a relation between the guidelines and the grounds of the court decisions and that there are different types of binding effects. To fulfill such purpose, the principles that guide the judges’ activities were analyzed: duty to decide, independence, and legal binding effect. We analyzed the binding effect of the guidelines in relation to the grounds of court decisions, based on eight ideal systems of formal relevance proposed by Pierluigi Chiassoni. We also analyzed the guidelines that are binding as a result of the Constitution, of the Law, and resulting from court practices and the process for reviewing the guidelines. The research has been conducted based on the legislation, the opinion of jurists on the subject, and courts case law. The conclusion embraces the existence of four levels of binding effect in relation to the utilization of guidelines in the grounds of court decisions and the existence of two types of binding effect (formal binding effect, resulting from the Constitution or from the Law, and the empirical binding effect, resulting from court practices)